Anterior Endocrowns as An Alternative to Core Crown restorations: A Systematic Review - Hisham A. Mously; Ghada H. Naguib; Ahmed O. Abougazia; Afaf A. Almabadi; Osama A. Qutub; Mohamed T. Hamed (International Dental Journal)
Restoring extensively damaged endodontically treated teeth presents a challenging task due to the state of biomechanical deterioration affecting long-term prognosis. Therefore, the study aims to assess and compare the biomechanical performance of endocrowns and post core-crown restorations in anterior endodontically treated teeth with severe coronal structure loss. Following PRISMA guidelines, a systematic search was conducted using PubMed, Scopus, Web of Science, and Google Scholar for articles published from January 2014 to March 2024. Two independent reviewers screened and selected studies based on the predefined inclusion and exclusion criteria. The included studies were analyzed using the QUIN tool for risk of bias assessment in in-vitro studies. Additionally, the biomechanical outcomes were collected for qualitative comparative analysis. Twelve studies were included in this systematic review. In most studies, Endocrowns demonstrated comparable fatigue resistance under load to failure to post core-crown restorations. Endocrowns without ferrule exhibited a higher rate of debonding but had significantly more repairable failures. Conversely, post core-crown restorations demonstrated higher fracture resistance with the presence of ferrule, but were associated with more catastrophic failure patterns. Additionally, endocrowns generated lower stress levels in both the restorative material and the luting material compared to post core-crown restorations. Among the tested materials, lithium disilicate ceramics provided the best biomechanical properties. Overall, the studies included provided sufficient information for most evaluation criteria of the QUIN risk of bias assessment tool. Endocrowns are a viable and conservative approach for restoring endodontically treated anterior teeth, offering comparable biomechanical performance to traditional post core-crown restorations and less catastrophic failures. The findings of this systematic review suggest that endocrown restorations, especially with lithium disilicate ceramics and proper ferrule design, can improve fracture resistance and longevity of rehabilitated teeth, enhancing patient outcomes for severely damaged anterior endodontically treated teeth.